Chain of care for patients who have attempted suicide: a follow-up study from Bærum, Norway - Claussen Bjørgulf; De Leo Diego; Dieserud Gudrun; Johannessen Håkon A; Zahl Per-Henrik (BMC, 2011)
Abstract Background Individuals who have attempted suicide are at increased risk of subsequent suicidal behavior. Since 1983, a community-based suicide prevention team has been operating in the municipality of Bærum, Norway. This study aimed to test the effectiveness of the team's interventions in preventing repeated suicide attempts and suicide deaths, as part of a chain of care model for all general hospital treated suicide attempters. Methods Data has been collected consecutively since 1984 and a follow-up was conducted on all individuals admitted to the general hospital after a suicide attempt. The risk of repeated suicide attempt and suicide were comparatively examined in subjects who received assistance from the suicide prevention team in addition to treatment as usual versus those who received treatment as usual only. Logistic regression and Cox regression were used to analyze the data. Results Between January 1984 and December 2007, 1,616 subjects were registered as having attempted suicide; 197 of them (12%) made another attempt within 12 months. Compared to subjects who did not receive assistance from the suicide prevention team, individuals involved in the prevention program did not have a significantly different risk of repeated attempt within 6 months (adjusted OR = 1.08; 95% CI = 0.66-1.74), 12 months (adjusted OR = 0.86; 95% CI = 0.57-1.30), or 5 years (adjusted RR = 0.90; 95% CI = 0.67-1.22) after their first recorded attempt. There was also no difference in risk of suicide (adjusted RR = 0.85; 95% CI = 0.46-1.57). Previous suicide attempts, marital status, and employment status were significantly associated with a repeated suicide attempt within 6 and 12 months (p < 0.05). Alcohol misuse, employment status, and previous suicide attempts were significantly associated with a repeated attempt within 5 years (p < 0.05) while marital status became non-significant (p > 0.05). With each year of age, the risk of suicide increased by 3% (p < 0.05). Conclusions The present study did not find any differences in the risk of fatal and non-fatal suicidal behavior between subjects who received treatment as usual combined with community assistance versus subjects who received only treatment as usual. However, assistance from the community team was mainly offered to attempters who were not receiving sufficient support from treatment as usual and was accepted by 50-60% of those deemed eligible. Thus, obtaining similar outcomes for individuals, all of whom were clinically judged to have different needs, could in itself be considered a desirable result.